“comportamiento agrónomico de ocho variedades introducidas de caña de azucar (saccharum officinarum) en el huallaga central” - Bartra García, Joe Christian (2009)
The present work titled Establishment and agronomic and industrial evaluation of local and introduced cultivares of cane of sugar ( Saccharum officinarum) in the Central Huallaga". he/she has as objectives: To evaluate the agronomic and industrial behavior of the introduced varieties of cane of sugar and local low conditions of the Central Huallaga. The investigation work was taken 1 end up in the Central Huallaga, specifically in the District of Puerto Rico in lands of the National University of San Martin - Tarapoto that dista to 73 Km of the city of Tarapoto. Located geographically: South latitude 06°12 ', Longitude west of 76°29 ' and an Altitude 310 m.s.n.m.m. political Location: District Puerto Rico, province Picota, County Pillory and Region San Martin. A Design of Blocks was used Randomizado Completely (DBCR) with 8 treatments (cultivares) and 4 repetitions, the cultivares was: CP74 - 2005, M64 - 1487, Blue Marries Big, M72 - 458, M72 - 458, RB72 - 454, M69 - 290, M69 -420 and Javanese (witness). The treatment T8 (Javanese Variety), it showed the best behavior represented in the best characteristic obtained biométricas, as shaft height, height of cane molible, number and entrenudos longitude, number of active leaves to the crop and cane yield; due mainly to the favorable environmental conditions for their development and to the adaptability demonstrated to those conditions (local Variety).